Current collapse modeling in AlGaN/GaN HEMT using small signal equivalent circuit for high power application. (January 2018) - Nirmal, D.; Arivazhagan, L.; Fletcher, A.S.Augustine; Ajayan, J.; Prajoon, P.
Abstract: In this paper, the drain current collapse in AlGaN/GaN High Electron Mobility Transistor (HEMT) with field plate engineering is investigated. A small signal equivalent circuit of AlGaN/GaN HEMT is developed and a new drain current model is derived. This model is useful to correlate the impact of intrinsic capacitance and conductance on drain current collapse. The proposed device suppressed the current collapse phenomena by 10% compared with the conventional AlGaN/GaN HEMT. Moreover, the DC characteristics of the simulated device shows a drain current of 900 mA/mm, breakdown voltage of 291 V and transconductance of 175 mS/mm. Besides, the intrinsic capacitance and conductance parameters are extracted and its impact on drain current is analysed. Finally, the simulation results obtained were in compliance with the derived mathematical model of AlGaN/GaN HEMT. Highlights: A drain current model for current collapse in AlGaN/GaN HEMT using small signal equivalent circuit. The incorporation field plate in the device achieved the breakdown voltage of 420 V. The drain current collapse is reduced by 10%. The impact of intrinsic capacitance and conductance parameters on drain current is analysed.